Framework de Aplicações Móveis com Segurança em SOA - FONSÊCA, Johnneth de Sene (2009)
The constant evolution of technologies used in mobile devices has increased its capabilities with respect to its storage, processing and transmission of data, including more of one kind of technology transfer in a single device, and also access Internet more efficiently. These factors have a greater number of applications and services may be provided therein. With this came the need to find a model for developing services and making them available more quickly and efficient, and that data is transmitted more securely. One of the best options currently existing are the SOAS (Services Oriented Architecture) a development model in great evidence today. The aim of this dissertation is present a framework that allows the development of SOA in the mobile environment, giving the developer all the tools necessary for provision of services in this type of environment. A tool for the use of security mechanism for the Framework is also proposed.